(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The desirable effects of such medications as Tadalafil and Bosentan on the right heart hemodynamics to treat the pulmonary hypertension of the patients with the exacerbation of chronic obstructive pulmonary disease under mechanical ventilation principally increase the cardiac output by increasing the left ventricular preload, as the effects of this increase are statistically valuable in improving the prognosis of the patients. For this, the present study investigates the non-invasive effects of these therapeutic agents (tadalafil and bosentan) on the pulmonary hypertension of the patients with the chronic obstructive pulmonary disease (COPD) who are under the mechanical ventilation. Procedure: This study was a randomized clinical trial that was carried out at the Imam Reza Hospital (Tabriz University of Medical Sciences, Iran) from 2018 to 2019, with the participation of 200 patients diagnosed with COPD and pulmonary arterial hypertension. Having been randomly assigned to two groups, the bosentan group received a 125 mg bosentan medication twice per day, while the tadalafil group received 40 mg tadalafil once per day, as before and after the intervention, stroke volume, left ventricle output and pulmonary arterial hypertension were measured and compared. Descriptive and inferential statistics were used for the comparison of the two groups, as the P level of less than 0.05 was significant. Results: Results indicated the significant effects of both drugs on reducing the pulmonary arterial hypertension, though the post-intervention inter-group comparison suggested no significant statistical difference between the two groups. On the other hand, both drugs created significant improvements of FEV1, PaO2 and PaCO2. However no significant difference was noted between the two groups in terms of the duration of the mechanical ventilation and the number of patients being successfully removed from ventilators. Conclusion: Tadalafil and bosentan were found to improve the oxygenation level, reduce pulmonary arterial hypertension and reduce the time needed for assisted ventilation.